MRXT: The Multi-Robot Exploration Tool. (2nd April 2015) - Gil, Arturo; Juliá, Miguel; Reinoso, Óscar
This paper presents the multi-robot eXploration tool (MRXT) [Freely available athttp://arvc.umh.es/mrxt ], a new mobile robotics simulation tool whose aim is to experiment and understand some well-known multi-robot exploration algorithms. The application is designed to test and compare different multi-robot exploration algorithms as well as SLAM techniques. The application includes a wide range of exploration algorithms that differ in their level of coordination and integration with the SLAM algorithm. The tool is focused on describing the exploration problem in a simple manner so that it is useful for educational or research purposes. In comparison with other simulation tools, MRXT is the first application completely focused on the exploration problem, so it can be easily employed to understand interactively many of the issues regarding this general problem in mobile robotics. Furthermore, the paper describes some examples using the tool.